2019
DOI: 10.31234/osf.io/h437v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Exploration Advantage: Children’s instinct to explore allows them to find information that adults miss.

Abstract: Humans have a long childhood in comparison to all other species. Across disciplines, researchers agree that humans’ prolonged immaturity is integral to our unique intelligence. The studies presented here support the hypothesis that human beings’ extended childhood pays off in the form of an ability to learn more about changing environments. Across two studies (n = 213), children and adults played a game where they chose among four different cartoon monsters yielding different numbers of star rewards. Adults fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 8 publications
0
50
0
Order By: Relevance
“…In a classic "multiarmed bandit task," participants choose over a number of trials between a fixed number of options, each of which produces a fixed reward (e.g., one option provides 3 candies and another option provides 8 candies). In this task, adults repeatedly choose the most rewarding option after a brief initial period of exploration, while children as young as 3 years old are more likely to persist in choosing both good and bad options throughout the task (Blanco & Sloutsky, 2019, 2020Sumner, Li, et al, 2019;Sumner, Steyvers, et al, 2019). Using a modified multiarmed bandit task, another study found that 7-to 11-year-olds showed more directed exploration (actively choosing options that resolve uncertainty) than adults.…”
Section: Exploration Across Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In a classic "multiarmed bandit task," participants choose over a number of trials between a fixed number of options, each of which produces a fixed reward (e.g., one option provides 3 candies and another option provides 8 candies). In this task, adults repeatedly choose the most rewarding option after a brief initial period of exploration, while children as young as 3 years old are more likely to persist in choosing both good and bad options throughout the task (Blanco & Sloutsky, 2019, 2020Sumner, Li, et al, 2019;Sumner, Steyvers, et al, 2019). Using a modified multiarmed bandit task, another study found that 7-to 11-year-olds showed more directed exploration (actively choosing options that resolve uncertainty) than adults.…”
Section: Exploration Across Developmentmentioning
confidence: 99%
“…In addition, very little research has investigated the connection between explore-exploit decision making and subsequent learning (but see Sumner, Li, et al, 2019). If children do explore more than adults across tasks, does this help them learn?…”
Section: Exploration Across Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The answer to this question is empirical. If our account does well in describing and predicting animal behavior, that would be some evidence for it ( Sumner et al, 2019 ; Wang and Hayden, 2019 ; Jaegle et al, 2019 ; Gottlieb and Oudeyer, 2018 ; Kidd and Hayden, 2015 ; Berlyne, 1950 ; Colas et al, 2020b ; Rahnev and Denison, 2018 ; Wilson et al, 2020 ; Cogliati Dezza et al, 2017 ; Berger-Tal et al, 2014 ). If it predicts neural structures ( Cisek, 2019 ; Kobayashi and Hsu, 2019 ), that would be some evidence for it (we discuss this more below).…”
Section: Discussionmentioning
confidence: 79%
“…The choice between exploring and exploiting is a kind of decision that is faced routinely by learners of all kinds, including foraging bees, business organizations, humans, worms, monkeys, rodents, birds, children, and computer algorithms ( Gupta et al, 2006 ; Sutton and Barto, 2018 ; Woodgate et al, 2017 ; Lee et al, 2011 ; Schulz et al, 2018 ; Calhoun et al, 2014 ; Wang and Hayden, 2019 ; Sumner et al, 2019 ; Auersperg, 2015 ). But is reward really fundamental to it?…”
Section: Figurementioning
confidence: 99%